Acupuncture in Oncology: The Effectiveness of Acupuncture May Not Depend on Needle Retention Duration. (June 2018) - Oh, Byeongsang; Eade, Thomas; Kneebone, Andrew; Hruby, George; Lamoury, Gillian; Pavlakis, Nick; Clarke, Stephen; Zaslawski, Chris; Marr, Isobel; Costa, Daniel; Back, Michael
Background. Guidelines surrounding optimum needle retention duration in acupuncture have not been established, despite a growing evidence base for acupuncture over recent decades. This retrospective study explored the effect of varying acupuncture needle retention durations in cancer patients. Method. Patients received either 2 (n = 35), 10 (n = 53), or 20 minutes (n = 54) of acupuncture once a week for 6 weeks. Outcomes of anxiety and depression, stress, fatigue, and quality of life (QOL), with the Hospital Anxiety and Depression Scale, Perceived Stress Scale, Functional Assessment of Cancer Therapy–Fatigue, and European Organization for Research and Treatment of Cancer Quality of Life, were measured at baseline and at 6 weeks following the intervention. Results. The mean age of participants was 58 years (n = 152). The majority were female, diagnosed with breast cancer. Depression, stress, fatigue, and QOL were significantly improved in all 3 groups at 6 weeks postintervention. No significant differences in all outcomes were found between the 3 groups (≤2 vs 10 minutes vs 20 minutes). There were no differences with the satisfaction of the acupuncture services and perceived efficacy of acupuncture among the 3 groups. More than 95% of participants indicated that they would recommend acupuncture to other cancer patients, friends, and their family members. Conclusion. The efficacy of acupuncture may not only depend on needle retention duration, but may also be associated with multiple factors. Considering the limitations of this study design, robust randomized controlled studies are warranted to confirm the findings.